Essential role of IκBNS for in vivo CD4+ T‐cell activation, proliferation, and Th1‐cell differentiation during Listeria monocytogenes infection in mice. Issue 9 (7th June 2019) - Frentzel, Sarah; Katsoulis‐Dimitriou, Konstantinos; Jeron, Andreas; Schmitz, Ingo; Bruder, Dunja
Abstract: Acquisition of effector functions in T cells is guided by transcription factors, including NF‐κB, that itself is tightly controlled by inhibitory proteins. The atypical NF‐κB inhibitor, IκBNS, is involved in the development of Th1, Th17, and regulatory T (Treg) cells. However, it remained unclear to which extend IκBNS contributed to the acquisition of effector function in T cells specifically responding to a pathogen during in vivo infection. Tracking of adoptively transferred T cells in Listeria monocytogenes infected mice antigen‐specific activation of CD4 + T cells following in vivo pathogen encounter to strongly rely on IκBNS . While IκBNS was largely dispensable for the acquisition of cytotoxic effector function in CD8 + T cells, IκBNS ‐deficient Th1 effector cells exhibited significantly reduced proliferation, marked changes in the pattern of activation marker expression, and reduced production of the Th1‐cell cytokines IFN‐γ, IL‐2, and TNF‐α. Complementary in vitro analyses using cells from novel reporter and inducible knockout mice revealed that IκBNS predominantly affects the early phase of Th1‐cell differentiation while its function in terminally differentiated cells appears to be negligible. Our data suggest IκBNS as a potential target to modulate specifically CD4 + T‐cell responses. Abstract : Combining adoptive transfer of T cells recognizing a pathogen‐derived antigen with in vivo Listeria monocytogenes infection in mice uncovered that the atypical NF‐κB inhibitor IκBNS is essential for antigen‐specific activation, in vivo expansion and Th1 cell differentiation of CD4 + T cells in infectious settings.